A meta-analysis of associations between obesity and insomnia diagnosis and symptoms. (August 2018) - Chan, Wai Sze; Levsen, Meredith P.; McCrae, Christina S.
Summary: Recent research suggests that sleep plays an important role in obesity (OB). No systematic reviews have investigated the association between OB and insomnia specifically. The present study reviewed the past 10 y of findings on the association between insomnia diagnosis (IND) and insomnia symptoms (INS) with OB. A total of 67 studies were included in the meta-analyses. Multilevel random effects models showed that the odds of having OB among those who had IND was not significantly greater than the odds of having OB among those who did not have IND (odds ratio (OR) = .80, p = .61). A small, significant cross-sectional correlation ( r = .06, p = .03) was found between INS and body mass index. Longitudinal data were limited. Based on three studies, the odds of developing future INS among those who had OB were not significantly greater than those who were normal-weight (NW) (OR = 1.07, p = .40). Longitudinal data on the association between INS and future incidence of OB are inconclusive. We found no indication of systematic publication biases and high heterogeneity in the effect sizes across studies. Meta-regressions showed that some of the heterogeneity was explained by the types of measures of insomnia symptoms, publication year, and regions where a study was conducted.